Identifying safe corridors for anterior pelvic percutaneous instrumentation using computed tomography-based anatomical relationships. Issue 10 (October 2022) - Green, Adam; Feldman, Guy; Moore, Daniel Shawn; Ashikyan, Oganes; Sims, Gina Cho; Sanders, Drew; Starr, Adam; Grewal, Ishvinder
Highlights: Percutaneous anterior pelvic ring instrumentation in traumatic pelvic injuries has the potential to reduce complications and decrease operative time. Better understanding of the anatomic relationships of critical structures around the anterior pelvic ring, such as the spermatic cord and round ligament can promote the safety and efficacy of anterior pelvic instrumentation. Eighty axial computed tomography scans of the abdomen obtained for non-traumatic patients were evaluated by three 3 fellowship trained radiologists. Safe corridors for percutaneous screw fixation of the anterior pelvic were documented. Using the data presented in this study the surgeon can better plan the procedure and decrease the chance of iatrogenic damage. Abstract: Introduction: Percutaneous anterior pelvic ring instrumentation is performed for retrograde screw fixation of ramus fractures, as well as for repair of pubic symphysis diastasis. The anatomic relationships of critical structures around the anterior pelvic ring, such as the spermatic cord and round ligament, have been described in only a few studies regarding the risk of iatrogenic injury during surgery. Our goal is to further describe these relationships, as well as provide radiographic information on safe corridors for percutaneous fixation. Methods: Eighty (80) axial computed tomography scans of the abdomen, obtained for non traumatic diagnostic purposes and screened for prior abdominal trauma or procedures, were evaluated by 3 fellowship trained radiologists. Mid-symphyseal cuts were used to obtain several measurements relative to the spermatic cords (SC) or round ligaments (RL): inter-cord or inter-ligament distance, skin to cortex of symphysis distance (vertical), skin to cortex of symphysis distance (oblique), safe corridor distance (between SC/RL and femoral triangle), center safe angle (relative to bilateral ischia), maximal safe angle, and minimal safe angle. Results: There were 41 male and 39 female scans included in the final analysis. The average inter-cord distance was 50.2 mm, skin to cortex vertical distance of 43.0 mm, skin to cortex oblique distance of 83.5 mm, safe corridor distance 26.3 mm, center safe angle 19.3˚, maximal safe angle 32.3˚, and minimal safe angle 13.6˚. These were further broken down by range and gender in Table 1. Agreement between radiologists was high for these different measurements with the exception of the skin to cortex oblique distance in female patients and the maximal safe angle in female patients, due to absence of round ligament in a majority of the scans. The round ligament was only present at the mid-symphyseal level for our three reviewers in 37/39, 36/39, and 24/39 of female patient scans. Conclusions: We have identified defined safe corridors for instrumentation of the anterior pelvic ring that can assist the surgeon in percutaneous application of fixation for fracture care.